2017
DOI: 10.1186/s12889-017-4808-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of arsenic exposure in young children and home water arsenic in two rural West Texas communities

Abstract: BackgroundIn a previously conducted Health Impact Assessment of a well-water dependent southwest community, arsenic (As) levels greater than the EPA Maximum Contaminant Level (10 μg/L) were identified in home water samples. The goals of this study were to test whether children from the previously studied well-water dependent community (Community 1) had higher blood As levels than children from a demographically similar and geographically nearby community dependent on a municipal water supply (Community 2); to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…These studies were included in our review because they assessed environmental metals exposure potential for a rural population in the study region. Two of these studies reported associations between environmental metals in water and markers of potential health effect [15, 16], and two other studies reported associations between As in water with levels in blood or nail clippings [17, 18]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies were included in our review because they assessed environmental metals exposure potential for a rural population in the study region. Two of these studies reported associations between environmental metals in water and markers of potential health effect [15, 16], and two other studies reported associations between As in water with levels in blood or nail clippings [17, 18]. …”
Section: Resultsmentioning
confidence: 99%
“…Sampling methods were conducted in a prospective fashion including one-time grab samples and repeat sample collection to observe seasonal variability. Chemical concentrations were measured using Inductively Coupled Plasma (ICP) – Optical Emissions Spectroscopy [15, 16, 1921], ICP – Atomic Emissions Spectroscopy [15, 16, 19, 20], ICP – Mass Spectroscopy [13, 1517, 1924], or Graphite Furnace Atomic Absorption Spectroscopy [18]. Additionally, concentrations of As, U, chromium (Cr), lead (Pb), iron (Fe), and vanadium (V) were measured in mine waste, soil, sediment and other solid material using x-ray fluorescence [21, 22], X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy [21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic arsenic toxicity, which is due to low-concentration exposure over a long period of time, impairs the same organs and tissues as acute toxicity, although in cases of higher exposure levels, skin and nervous system disturbances are usually more pronounced (Lagerkvist and Zetterlund 1994 ; Ahsan et al 2006 ; Naujokas et al 2013 ). Chronic arsenic intoxication has been caused not only by drinking contaminated groundwater (Mazumder et al 1998 ; Milton and Rahman 2002 ; Chakraborti et al 2003 ; Otto et al 2006 ; Chen 2014 ; Del Rio et al 2017 ; Rehman et al 2018 ) but also by occupational exposures, such as mining (Ishinishi et al 1977 ; Kawasaki et al 2002 ; Eisler 2004 ) and work with copper smelters (Feldman et al 1979 ; Lubin et al 2008 ; Halatek et al 2009 ; Sinczuk-Walczak et al 2010 ).…”
mentioning
confidence: 99%